Physical mapping of four serpin genes: alpha 1-antitrypsin, alpha 1-antichymotrypsin, corticosteroid-binding globulin, and protein C inhibitor, within a 280-kb region on chromosome I4q32.1. - Billingsley, G D (1993)
Alpha 1-antitrypsin (alpha 1AT; protease inhibitor [PI] locus), alpha 1-antichymotrypsin (alpha 1ACT; AACT locus), corticosteroid-binding globulin (CBG; CBG locus), and protein C inhibitor (PCI; PCI locus) are members of the serine protease inhibitor (serpin) superfamily. A noncoding PI-like (PIL) gene has been located 12 kb 3' of the PI gene. The PI, PIL, and AACT loci have been localized to 14q32.1, the CBG locus has been localized to 14q31-14q32.1, and PCI has been mapped to chromosome 14. Genetic linkage analysis suggests tight linkage between PI and AACT. We have used pulsed-field gel electrophoresis to generate a physical map linking these five serpin genes. The order of the genetic loci is AACT/PCI-PI-PIL-CBG, with a maximum distance of about 220 kb between the AACT/PCI and PI genes. These genes form a PI cluster at 14q32.1, similar to that of the homologous genes on murine chromosome l2. The close proximity of these genes has implications for disease-association studies.